Insights into the origins of guided microtrenches and microholes/rings from Sn segregation in germanium–tin epilayers - Wu, Shaoteng (2020)
We demonstrate the self-assembly synthesis of millimetre-long guided trenches and micro-holes/rings in the supersaturated GeSn epilayers through two approaches: epitaxial growth engineering and thermal annealing treatment. It reveals that the ordered trenches originate from a central nucleation point which typically accompanied by micro-hole/ring formation. These trenches are caused by the migration of Sn droplets on the film surface with the orientation dominantly along <100> or <110>axis, determined by the Sn-content of the epilayers and formation temperature. The holes/rings are postulated to be caused by the local droplet etching due to the development of Ge-Sn eutectic. The morphological and compositional evolution of the Sn-segregation is characterized by the combination of optical and electronic microscopy, spectroscopy, and atomic force microscope measurements. This work provides a comprehensive understanding of the mechanism for the Sn segregation in GeSn and suggests the new degree of freedom to the growth and engineering of droplet-assisted micro-structures.